From “self-differentiation” to organoids—the quest for the units of development - Schlosser, Gerhard (Development genes and evolution, 2024)
As proposed by Wilhelm Roux in 1885, the key goal of experimental embryology (“Entwicklungsmechanik”) was to elucidate whether organisms or their parts develop autonomously (“self-differentiation”) or require interactions with other parts or the environment. However, experimental embryologists soon realized that concepts like “self-differentiation” only make sense when applied to particular parts or units of the developing embryo as defined both in time and space. Whereas the formation of tissues or organs may initially depend on interactions with surrounding tissues, they later become independent of such interactions or “determined.” Moreover, the determination of a particular tissue or organ primordium has to be distinguished from the spatially coordinated determination of its parts—what we now refer to as “patterning.” While some primordia depend on extrinsic influences (e.g., signals from adjacent tissues) for proper patterning, others rely on intrinsic mechanisms. Such intrinsically patterned units may behave as “morphogenetic fields” that can compensate for lost parts and regulate their size and proper patterning. While these insights were won by experimental embryologists more than 100 years ago, they retain their relevance today. To enable the generation of more life-like organoids in vitro for studying developmental processes and diseases in a dish, questions about the spatiotemporal units of development (when and how tissues and organs are determined and patterned) need to be increasingly considered. This review briefly sketches this conceptual history and its continued relevance by focusing on the determination and patterning of the inner ear with a specific emphasis on some studies published in this journal.